RESTRICTIONS OF HUMAN RIGHTS UNDER THE EUROPEAN CONVENTION OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS - new tendencies - Toroman, Aleksandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The majority of human rights can be restricted in certain situations, despite their significance for every democratic society. That means that those rights are not absolute. Such situations represent, for example, war and states of emergency, according to the European Convention on Human Rights. Then, in order to protect the interest of the state and national security, human rights, that means the interests of individuals, come second. In that case, it is necessary to achieve a balance between the necessary restrictions and the preservation of the state’s interests. One of the best examples of the restrictions of human rights during a state of emergency is the period of Covid-19. Many rights, such as right to respect for private and family life, were restricted during Covid-19 in a variety of countries in Europe, but each country established its own measures according to its own situation. The cases regarding these restrictions and violations will be presented before the European Court of Human Rights in the years to come.